Analisis Perilaku Mahasiswa Manajemen dalam Kaitannya dengan Hasil Ujian Komunikasi Bisnis (Studi Mahasiswa pada Mahasiswa Manajemen Unjani) - Irawan, Andri (Jurnal Bisnis Darmajaya, 2015)
The world of education today face the challenge to make a real contribution in solving the existing problems. Students as the next generation in the continuing development phases have a duty to be able to contribute ideas in the form of real work. UNJANI Management Faculty of Economics is one of the courses that are in west Java Cimahi.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  The purpose of this study was to determine the extent of the difference in behavior of student learning at the Department of Management Business Communication course. The purpose of this analysis was to compare the two averages two unrelated groups. The data used is quantitative assuming normal distribution. The sample in this study amounted to 68 people and is divided into two groups, each numbering 34 people. Statistical analysis tool used is a non-parametric statistical test form independent sample test. Based on the results of statistical data if the result is that there are significant differences between the test results of the two groups of students of this can be seen from the Sig smaller than alpha is 0.013 <0.05. The results of the test group of students who received treatment with no prior information about the execution of the test to get a better result than the test results of students who obtain information on the previous exam. This is due to the different behavior is that some students perform regularly set aside time to study and some will not.Key word âbehavior of student, exam results, business communication